Nano Particles: A Novel System In Current Century - M, Suganeswari (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTNanoparticles are defined as particulate dispersions or solid particles with a size in the range of 10-1000 nm. The drug is dissolved, entrapped, encapsulated or attached to a nanoparticle matrix. The major goals in designing nanoparticles as a delivery system are to control particle size surface properties and release of pharmacologically active agents in order to achieve the site-specific action of the drug at the therapeutically optimal rate and dose regimen. For the past few decades, there has been a considerable research interest in the area of drug delivery using particulate delivery systems as carriers for small and large molecules. Particulate systems like nanoparticles have been as physical approach to alter and improve the pharmacokinetic and pharmacodynamic properties of various types of drug molecules. Particle size and surface characteristic of nanoparticle can be easily manipulated to achieve both passive and active drug targeting after parental administration. They have been used in vivo the drug entity in the systemic circulation, restrict access of the drug to the chosen sites and to deliver drug at a controlled and sustained rate to the site of action. Various polymers have been used in the formulation of nanoparticles for drug delivery research to increase therapeutic benefit, while minimizing side effects. Here, we review various aspects of nanoparticle formulation, characterization, effect of their characteristics and their applications in delivery of drug molecules and therapeutic genes.